2022
DOI: 10.54029/2022rtm
|View full text |Cite
|
Sign up to set email alerts
|

Association of obstructive sleep apnea syndrome with hematological parameters and comorbid diseases

Abstract: Background & Objective: Obstructive sleep apnea syndrome (OSAS) has a close relationship with many diseases. Hematological parameters are simple diagnostic methods and can give an idea about severity of some diseases. The aim of this study was to examine the relationship of OSAS with comorbid diseases and relationship between OSAS severity, oxygen desaturation index (ODI) and hematological parameters. Methods: This retrospective and cross-sectional study was conducted by evaluating the medical files of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The prevalence of comorbidities in severe OSA may increase because of the higher level of systemic inflammation. In a retrospective study of 1,119 patients, the NLR and PLR were reported to be significantly higher in OSA patients with chronic obstructive pulmonary disease, asthma, and congestive heart failure [ 22 ]. Similarly, a metaanalysis showed that the NLR was higher in patients with OSA than in normal controls [ 9 ] and decreased after continuous positive airway pressure [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of comorbidities in severe OSA may increase because of the higher level of systemic inflammation. In a retrospective study of 1,119 patients, the NLR and PLR were reported to be significantly higher in OSA patients with chronic obstructive pulmonary disease, asthma, and congestive heart failure [ 22 ]. Similarly, a metaanalysis showed that the NLR was higher in patients with OSA than in normal controls [ 9 ] and decreased after continuous positive airway pressure [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 48 were removed because they did not report the studied endpoint (n = 30), did not include the control group (n = 9), investigated pediatric cohorts (n = 4) or different patient groups (n = 2), or were not written in English (n = 3), leaving 17 articles. Since three additional records were identified from Google Scholar and reference lists, a total of 20 manuscripts [14,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] were included in the final analysis (Figure 1). The included studies were published between 2012 [44] and 2022 [60][61][62].…”
Section: Systematic Research and Study Characteristicsmentioning
confidence: 99%
“…Since three additional records were identified from Google Scholar and reference lists, a total of 20 manuscripts [14,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] were included in the final analysis (Figure 1). The included studies were published between 2012 [44] and 2022 [60][61][62]. The majority were conducted in Turkey (n = 15) [14,[44][45][46][47][48]52,54,55,57,58,60,62], whereas the remaining (n = 5) were conducted in Spain [49], Egypt [50], Pakistan [53], China [56], and Romania [61].…”
Section: Systematic Research and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations